Reaksi Pasar atas Pengumuman Suku Bunga the Fed pada Sektor Perbankan yang Terdaftar di Indonesia - Reziario Nugraha, Amadeus Vincent; Ary Wirajaya, I Gede (E-Jurnal Akuntansi, 2023)
This study aims to find out and test the market reaction around the announcement date indicated by abnormal returns around the date, to find out and test the market reaction around the announcement date indicated by trading volume activity around the date, and to find out and test the differences in the sample t-test. This research involved 46 banks listed on the Indonesia Stock Exchange. The method of determining the sample used in this study is by using a saturated sample where all members of the population are sampled. This study uses secondary data from the financial statements of banking companies listed on the IDX. Testing the data using the average difference test method. The results of the study show that there is no significant difference in abnormal returns before and after the announcement of the increase in the FED interest rate by the FOMC in the banking sector in Indonesia. Tests on trading volume activity show that there are significant differences in transaction volume before and after the announcement of the increase in the FED interest rate by the FOMC in the banking sector in Indonesia. Keywords: Fed Fund Rate; Abnormal Return; Total Volume Activity